(untitled) (Asian Journal of Agriculture, 2024)
Abstract. Al-Garory NH, Al-Musa RS, Al-Hashimi AG. 2025. Effect of selenium and zinc fortification on the physiochemical and sensory properties of Iraqi soft cheese. Asian J Agric 9: 52-59. Food industries, including the dairy industry, have developed to improve the health condition as they are the foods that provide the body with important nutritional components such as minerals, whose levels decrease after industrialization processes. This study aimed to evaluate the impact of fortifying Iraqi soft cheese with zinc and selenium. The study focused on the physicochemical properties, rheological behavior and sensory characteristics of the cheese along with peroxide value as an indicator of oxidative stability. Zinc and selenium elements were added at a concentration of 200 mg/L to milk for cheese making. The result showed that an increase in peroxide value with increasing storage time and a decrease in fat oxidation for zinc and selenium were noted in treatments compared to the control treatments made from buffalo milk (T1) and cow’s milk (T2). This may be due to the presence of selenium and zinc, which reduce fat oxidation, and lower pH values after storage. No effect of selenium and zinc fortification was observed on the acidity values of cheese, while the chemical composition values varied as selenium fortification did not affect the percentage of fat and protein. Microbial tests also showed an increase in bacteria number after 10 days of storage compared to the samples after manufacturing, as well as increase in total bacterial number after fortification. The hardness and consistency of cheese increased during storage and after addition of minerals compared to control samples. Cheese flexibility decreased after storage and fortification. The sensory indicators were almost similar in control and fortified samples.